A Review of Ethical Discussions on Platforms and Ecosystems - Hyrynsalmi Sami; Koskinen Jani; Hyrynsalmi Sonja (Germany, 2022)
Since the breakthrough of Apple’s iOS platform and AppStore market-place a decade ago, different kinds of ecosystems and platforms have conquered the world. In the ecosystem-based business model, a platform owner offers a technological solution (e.g., Apple, Google) for end-users (e.g., smart phone users) and producers (e.g., application and content developers). The platform owner benefits, either directly or indirectly, from the transactions between end-users and producers taking place in the platform. As the ecosystem-based model has gained popularity and de facto status in the industry, also critical voices in ethical problems and questions for the new model has raised. This paper reviews recent literature (n=20) on ethical discussion on platforms and ecosystems in order to summarise the current development and suggest some future avenues. The review show that several disciplines, from law to technology ethics and sociology, are addressing the same phenomena from different viewpoints. However, further studies are requested to support the building of a comprehensive view on complex concerns.
Proceedings of the Third Seminar on Technology Ethics 2019